Effect of Heat Treatment on the Grain Orientation of Bi3.25Nd0.75Ti3O12 Ceramics - Al-Amani, Umar (Universiti Putra Malaysia, 2011)
Neodymium substituted-bismuth titanate, Bi3.25Nd0.75Ti3O12 (BNT075) ceramic was prepared using soft combustion technique. The dependence of heat treatment on the grain orientation of ceramic was observed. With increasing temperature, the BNT075 ceramic turned from off-c-axis-preferential-oriented to c-axis-oriented. The result also corresponded to the change from equiaxed structure to plate-like structure, indicating that the grain orientation had a significant influence on grain growth.